Not just surveys and indicators: narratives capture what really matters for health system strengthening - Oluoch, D; Molyneux, S; Boga, M; Maluni, J; Murila, F; Jones, C; Ziebland, S; English, M; Hinton, L (Elsevier, 2023)
Health system strengthening remains elusive and challenging. Health systems in many countries in sub-Saharan Africa are frequently characterised as weak, with inadequate management and accountability mechanisms, and poor human and financial resources. Putting patients and staff at the heart of health systems is an essential step towards strengthening them. As one of the three pillars of quality in health care, understanding patient experiences is key to moving towards people-centred care. Yet patient experiences are not a singular concept. Patient narratives can convey individual experiences of illness and health care, which complement and augment epidemiological and public health evidence. These narratives, gathered with rigorous, interview-based research and shared with digital tools (audio and video), can generate persuasive evidence. This evidence has important potential for influencing policy and practice, and for supporting people-centred care, but has not been tested systematically in low-income countries. In the Kenyan context of newborn health, work under way is generating evidence to show the transformative potential of patient narratives.